2012
DOI: 10.1353/not.2012.0131
|View full text |Cite
|
Sign up to set email alerts
|

Job Trends in Music Librarianship: A Nine-Year Analysis of the Music Library Association's Job List

Abstract: This study examines employment distribution for both professional and nonprofessional positions in music librarianship. Data were collected from the Music Library Association's Job Placement Service's Job List postings from 2002 through 2010. The 700 advertised positions are categorized by primary responsibilities, the hiring institution, and whether or not the position required an American Library Association-accredited master's degree in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Job advertisements for library staff provide an understanding of the library labor market, and job seekers can learn about the SKAs required to work at the library from the job advertisements (Clark, 2012; Messum et al. , 2016).…”
Section: Literature Review On Job Advertisements and Lis Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Job advertisements for library staff provide an understanding of the library labor market, and job seekers can learn about the SKAs required to work at the library from the job advertisements (Clark, 2012; Messum et al. , 2016).…”
Section: Literature Review On Job Advertisements and Lis Educationmentioning
confidence: 99%
“…2. Literature review on job advertisements and LIS education 2.1 Studies on job advertisements in the LIS field Job advertisements for library staff provide an understanding of the library labor market, and job seekers can learn about the SKAs required to work at the library from the job advertisements (Clark, 2012;Messum et al, 2016). Studies on job advertisements in the LIS field have been conducted for a long time (Harper, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The author developed criteria for determining which job postings would be included in the study and included both professional and nonprofessional positions. 7 Margaret Butler's 2008 study of interlibrary loan, document delivery and electronic reserves positions included job descriptions from a variety of library types, including large and small public libraries, a large academic library, and academic law libraries. 8 The author found that a variety of competencies were touched upon and that the description of copyright and ethics was a component to some of the job descriptions in this pool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utility of job advertisements can be understood by observing the growing number of studies that analyze the contents of job advertisements at a given time to look into the state of the job market for a given profession. The content analysis of job advertisements helps understand the job market and identify current skill requirements of various professions (Clark, 2012;Messum et al, 2016).…”
Section: Introductionmentioning
confidence: 99%